Kuzmenko A.G. Development of methods of contact mechanics shear concise surface. Part 2 - Кузьменко, А.Г. (Problems of Tribology, 2014)
In the study of shear surfaces compressed established communication friction stress function to the process with the stress distribution on the surface. Described and explained the mechanism of two sliding Friction and climb of synchronous.